Evaluating Livability in Green High-Rise Housing: A Resident-Centered Evaluation in the National Capital Region, India - Khurram Ashraf; Subhrajit Banerjee; Zeba Nisar (The Bioscan, 2024)
The population of India’s cities is projected to surge from 340 million in 2008 to 590 million by 2030, and the demand for affordable housing is expected to exceed supply by four times by 2030, according to a study by McKinsey Quarterly. In response tothe burgeoning urbanizationand land scarcity in India, high-rise apartments have emerged as a solution to housing shortages, driven by rising incomes and aspirations for improved lifestyles. Despite their touted sustainability benefits, assessing the Livability in these high-rise environments remains crucial.This study employs a scientific approach to evaluate the livability in high-rise housing within India's National Capital Region (NCR), examining factors such as safety, social cohesion, infrastructure, environmental sustainability, accessibility, and service provision. By integrating resident feedback and conducting comprehensive assessments of existing infrastructures, this research aims to provide evidence-based insights to inform urban planning strategies and recommend targeted interventions for enhancing overall livability in high-rise residential settings. Furthermore, the study seeks to address the unique challenges posed by high-rise living, including issues of community integration and sustainable resource management, to foster vibrant and resilient urban communities. By employing a mixed-methods approach, the research integrates quantitative and qualitative data to provide a comprehensive analysis of resident satisfaction. The study focuses on three green high-rise housing complexes in NCR region of India: Gaur Grandeur, Sector 119, Noida, ABA Cleo County, Sector 121, Noida, and Mahagun Moderne, Sector 78, Noida. The findings aim to offer actionable insights for developers, urban planners, and policymakers to enhance living conditions in urban high-rise environments.